Preparation method and application of multilayer carbon sphere material

By using the preparation method of multi-layer carbon ball material, the problem of insufficient wave absorption performance of traditional carbon materials is solved by using silica cores and polyacrylic acid-modified phenolic resin shells, and the efficient wave absorption performance of multi-layer carbon ball materials in a wide frequency band is achieved.

CN119873798AActive Publication Date: 2025-04-25FUZHOU UNIV

Patent Information

Application Number
CN202510182871.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-25
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

Traditional carbon materials have shortcomings in their absorption performance, such as narrow absorption frequency bands and insufficient absorption strength, which are difficult to meet the demand for high-performance absorbing materials in modern electronic technology and military fields.

Method used

Using the preparation method of multi-layer carbon sphere material, by repetitively alternately wrapping and carbonization treatment, the silica core is finally removed to obtain multi-layer hollow carbon spheres.

Benefits of technology

The prepared multi-layer carbon sphere material has excellent absorbance performance and can achieve efficient absorbance in a wide frequency band. In the specific example, the reflection loss of 500nm double-layer hollow carbon sphere reaches -43.87dB at 9.60GHz, and the effective absorbance bandwidth is 6.00GHz.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873798A_ABST
    Figure CN119873798A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a multi-layer carbon sphere material, a hollow carbon sphere is obtained by a hard template method, silicon dioxide is taken as a core, phenolic resin (RF) is taken as a shell, the silicon dioxide and the phenolic resin are repeatedly and alternately wrapped, and finally the multi-layer hollow carbon sphere can be obtained by carbonization and core removal. The multi-layer carbon spheres with different particle sizes can be obtained by adjusting the particle size of the silicon dioxide, and the layer number of the multi-layer hollow carbon spheres can be adjusted by adjusting the layer number covered by the phenolic resin. By means of reflection and scattering of the hollow structure of the hollow carbon sphere on electromagnetic waves and interface polarization among the multiple shell layers, the multilayer hollow carbon sphere has an excellent absorption effect on the electromagnetic waves. A novel preparation method is provided for the multilayer hollow carbon spheres, single-layer, double-layer and three-layer carbon spheres with different particle sizes are successfully prepared, the synthesis method is simple and convenient, the raw materials are low in price, and the obtained material has wide application prospects in the aspect of stealth technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wave absorbing materials, and in particular to a preparation method and application of a multilayer carbon ball material. Background Art

[0002] With the rapid development of modern electronic technology, electromagnetic radiation pollution is becoming increasingly serious. At the same time, in the military field, in order to counter radar detection, the demand for high-performance absorbing materials is also extremely urgent. Carbon materials have great application potential in the field of absorbing materials due to their unique electrical, magnetic and chemical properties. However, traditional carbon materials still have some shortcomings in terms of absorbing performance, such as narrow absorption band and insufficient absorption intensity. Therefore, it is of great significance to develop new carbon-based absorbing materials.

[0003] So far, the preparation method of hollow carbon spheres has made a breakthrough progress, mainly by using the structural guidance effect and structural order of the template, and controlling the internal structure of the synthesized material by changing the size and shape of its internal pore space. According to the different templates selected, it can be divided into hard template method, soft template method and template-free method. The hard template method is a method of preparing hollow carbon spheres using hard materials as templates. In the process of preparing hollow carbon spheres, it is necessary to first synthesize the template, fill the carbon precursor on the surface and in the pores of the template, and then carbonize it at high temperature. Then, according to the chemical properties of the template, the template is removed by calcination, decomposition or etching to obtain hollow carbon spheres with reverse replication of the template structure. Under ideal conditions, after the template is removed, the material can maintain the original pore structure morphology; the soft template method refers to a method of preparing hollow carbon spheres using soft materials as templates; among them, soft templates refer to organic molecules or supramolecular molecules with "soft" structures and high amphiphilicity, such as block copolymers, surfactant micelles, emulsion droplets, bubbles, etc., which can be used as soft templates for preparing ordered structure carbon materials. The main advantage of the soft template preparation method is that its template is relatively easy to remove. However, since the soft template is easy to deform, it may cause uneven morphology and size dispersion of hollow carbon spheres; the template-free method is that no prepared template is added during the preparation process, and there is no later template removal, and the preparation process is relatively simple. However, this method requires a strict reaction system, and trace impurities may affect the self-assembly behavior. These shortcomings make its practical application more difficult. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing multilayer carbon spheres, wherein the three-layer carbon spheres prepared by the method have a unique structure and excellent wave absorbing performance. Another object of the present invention is to provide the application of the multilayer carbon spheres in wave absorbing materials.

[0005] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing a multilayer carbon sphere material. The multilayer carbon sphere material uses silicon dioxide as a core and a phenolic resin modified by polyacrylic acid as a shell. Multilayer hollow carbon spheres are obtained by repeatedly and alternately wrapping silicon dioxide and phenolic resin, carbonizing them, and then removing the silicon dioxide core.

[0006] The particle size of the silicon dioxide is 70-1000 nm.

[0007] The specific steps of the multilayer carbon sphere material preparation method are as follows: (1) Synthesis of silicon dioxide: Anhydrous ethanol, deionized water, ethyl orthosilicate, ammonia water and potassium chloride are mixed and stirred to obtain a silicon dioxide emulsion; (2) Synthesis of SiO2@RF: resorcinol and formaldehyde were added to the silica emulsion obtained in step (1), stirred for reaction for 18 h and then centrifuged. The obtained solid was dried at 80°C for 12 h and crushed to obtain SiO2@RF powder. (3) Polyacrylic acid modified SiO2@RF: After dissolving SiO2@RF powder in deionized water, polyacrylic acid was added to react. After the reaction, the solution was centrifuged and the washed solid was redissolved in deionized water to obtain a polyacrylic acid modified SiO2@RF solution. (4) Synthesis of SiO2@RF@SiO2: add anhydrous ethanol, aqueous ammonia and ethyl orthosilicate to the solution obtained in step (3) and stir for 30 minutes to obtain an emulsion; (5) Synthesis of SiO2@RF@SiO2@RF: resorcinol and formaldehyde were added to the emulsion obtained in step (4), stirred for reaction for 18 h, and then centrifuged. The obtained solid was dried at 80°C for 12 h and crushed to obtain SiO2@RF@SiO2@RF powder. (6) Carbonization to form SiO2@C@SiO2@C: The powder obtained in step (5) is placed in a tube furnace, heated to 1000°C at a heating rate of 5°C / min in a nitrogen atmosphere, and reacted for 2 hours. After cooling to room temperature, SiO2@C@SiO2@C is obtained; (7) placing the SiO2@C@SiO2@C obtained in step (6) in an aqueous sodium hydroxide solution and reacting at 80°C for 24 hours, filtering the solution after the reaction, washing it to neutrality, and drying it to obtain double-layer hollow carbon spheres; (8) Repeat steps (3) to (7) with the SiO2@RF@SiO2@RF obtained in step (7) to obtain a three-layer hollow carbon sphere.

[0008] Furthermore, in step (1), the amounts of anhydrous ethanol, deionized water, tetraethyl orthosilicate, aqueous ammonia, and potassium chloride are 1500 mL: 210 mL: 68.4 mL: (20-200 mL): (0.2-4.4 g).

[0009] Furthermore, in step (2), the amount of resorcinol and formaldehyde used is 12 g:16.8 mL.

[0010] Furthermore, in step (3), the ratio of SiO2@RF powder to polyacrylic acid is 1:1.

[0011] Furthermore, in step (4), the dosage ratio of anhydrous ethanol, aqueous ammonia and tetraethyl orthosilicate is 200 mL:10 mL:1 mL.

[0012] Furthermore, the concentration of the sodium hydroxide solution in step (7) is 0.5 g / mL.

[0013] The present invention also provides multilayer hollow carbon spheres obtained by the above preparation method.

[0014] The present invention also provides a method for adjusting the particle size of silicon dioxide, and the specific steps are as follows: (1) Synthesis of 70-450nm silica particles: Add 1500ml of anhydrous ethanol, 210ml of deionized water, 68.4ml of ethyl orthosilicate and ammonia water into a beaker and stir for 30 minutes. After the reaction is completed, a white silica emulsion can be obtained. The amount of ammonia water is adjusted from 20ml to 200ml, and the silica particle size ranges from 70nm to 450nm.

[0015] (2) Synthesis of silica with a particle size of 450-800 nm: 1500 mL of anhydrous ethanol, 210 mL of deionized water, 68.4 mL of ethyl orthosilicate, 800 mL of ammonia water and potassium chloride were added into a beaker and stirred for 30 minutes to obtain a white silica emulsion. The amount of potassium chloride was adjusted from 0.2 to 1.4 g and the silica particle size was adjusted from 450 nm to 800 nm.

[0016] (3) Synthesis of 800-1000 nm silica: Add 750 mL of anhydrous ethanol, 105 mL of deionized water, 34.2 mL of tetraethyl orthosilicate, 400 mL of ammonia water and 0.75 g of potassium chloride into a beaker and stir for 30 minutes. Then, add another 750 mL of anhydrous ethanol, 105 mL of deionized water, 34.2 mL of tetraethyl orthosilicate and 0.75 g of potassium chloride into another beaker and add them into the first beaker at a rate of 1 mL / min. The addition time was adjusted from 0 to 900 min. The silica particle size ranged from 800 nm to 1000 nm.

[0017] In the present invention, in order to obtain hollow carbon spheres of different particle sizes, silicon dioxide of different particle sizes must be obtained first. The present invention is designed to produce silicon dioxide by using the sol-gel method, and the amount of ammonia water is adjusted, potassium chloride is added, and a seed growth method is used to obtain silicon dioxide of different particle sizes, and the particle size adjustment range is 70 nanometers to 1000 nanometers.

[0018] Phenolic resin is synthesized from resorcinol and formaldehyde. When resorcinol and formaldehyde are added to a silica gel solution, the resulting phenolic resin will adhere to the surface of silica, forming a core-shell structure SiO2@RF with silica as the core and phenolic resin as the shell. The thickness of the phenolic resin shell can be easily changed by changing the amount of resorcinol and formaldehyde, thereby obtaining hollow carbon spheres with different shell thicknesses. The above-mentioned core-shell structure SiO2@RF is carbonized in a nitrogen atmosphere at high temperature to convert the phenolic resin shell into a carbon shell, and then the silica is removed with an excess of sodium hydroxide to obtain hollow carbon spheres.

[0019] In order to enable silica to be repeatedly wrapped on the surface of phenolic resin without self-nucleation, this paper adopts a surface modification method to modify the phenolic resin using polyacrylic acid to achieve this effect.

[0020] The beneficial effects of the present invention are: The present invention provides a method for preparing hollow carbon spheres with different particle sizes, and a novel method for preparing double-layer and triple-layer hollow carbon spheres. In the conventional sol-gel method, adjusting the concentration of ammonia water can only make the particle size of silicon dioxide 450nm, while the present invention adds potassium chloride, and since potassium ions are positively charged and adsorbed on the surface of silicon dioxide, the repulsion between silicon dioxide can be reduced by neutralizing the surface charge of silicon dioxide, thereby promoting the aggregation and growth of silicon dioxide. In the process of seed particle growth, the formation of secondary particles usually leads to the distribution of different particle sizes. In order to suppress this, the supersaturation consumption rate of seed particle growth should be sufficient to exhaust the generation rate. The seed growth method adopts a low flow feed rate to reduce the supersaturation generation rate. This strategy allows silicon dioxide to continue to grow rather than form secondary particles; in addition, the surface of the phenolic resin shell layer is negatively charged, and the growth of silicon dioxide is also negatively charged. By adding polyacrylic acid, the negatively charged silicon dioxide can be surface modified, so that silicon dioxide can then grow on the surface of the phenolic resin. Multi-layer carbon spheres can be obtained by this multi-layer coating method. Since multilayer carbon spheres have better impedance matching and interface polarization performance than single-layer carbon spheres, the 500nm double-layer hollow carbon spheres finally screened have a minimum reflection loss RLmin of -43.87dB at 9.60GHz when the paraffin filling ratio is 20% and the thickness is 2.5mm, and the effective absorption bandwidth EAB is 6.00GHz (8.64-14.64GHz). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 SEM images of hollow carbon spheres with different particle sizes; (a) 70nm, (b) 300nm, (c) 500nm, (d) 650nm, (e) 1000nm; (f) TEM image of 300nm hollow carbon spheres; Figure 2TEM image of 500nm hollow carbon spheres after modification with polyacrylic acid (a), TEM image of 500nm hollow carbon spheres without polyacrylic acid modification (b); Figure 3 TEM images of 500nm hollow carbon spheres with different numbers of layers: single layer (a), double layer (b), and triple layer (c); Figure 4 Fourier transform infrared spectra of SiO2@RF before and after modification with polyacrylic acid; Figure 5 RL curve of 70nm single-layer hollow carbon sphere with 20% filler ratio in the frequency range of 2-18GHz; Figure 6 The RL curve of 300nm single-layer hollow carbon sphere with 20% filler ratio in the frequency range of 2-18GHz; Figure 7 RL curve of 500nm single-layer hollow carbon sphere with 20% filler ratio in the frequency range of 2-18GHz; Figure 8 This is the RL curve of 650nm single-layer hollow carbon sphere with 20% filler ratio in the frequency range of 2-18GHz; Fig. 9 RL curve of 1000nm single-layer hollow carbon sphere with 20% filler ratio in the frequency range of 2-18GHz; Fig.10 RL curve of 500nm double-layer hollow carbon sphere with 20% filler ratio in the frequency range of 2-18GHz; Fig.11 This is the RL curve of 500nm three-layer hollow carbon spheres with a filler ratio of 20% in the frequency range of 2-18GHz. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The exemplary implementation modes of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0023] Example 1 (1) Synthesis of silica: 1500 mL of anhydrous ethanol, 210 mL of deionized water, 68.4 mL of ethyl orthosilicate and 20 mL of ammonia water were added into a beaker and mixed and stirred for 30 minutes to obtain a white silica emulsion with a silica particle size of 70 nm. (2) Synthesis of SiO2@RF: 12 g of resorcinol and 16.8 mL of formaldehyde were added to the silica emulsion synthesized in step (1). The reaction was continued with stirring for 18 hours, and then the solid was centrifuged and dried in an oven at 80°C for 12 hours. The yellow SiO2@RF was then ground into powder using a mortar.

[0024] (3) Carbonization to form SiO2@C: The ground powder in step (2) is placed in an alumina square porcelain boat, which is then placed in a tubular furnace, connected to nitrogen, and heated to 1000°C at a heating rate of 5°C / min, and carbonized at 1000°C for 2 hours. When the temperature in the tubular furnace naturally cools down to room temperature, black SiO2@C is obtained.

[0025] (4) Removal of silica core: 60 g of sodium hydroxide was dissolved in 120 mL of deionized water to obtain a sodium hydroxide solution. Then, 30 g of SiO2@C obtained in step (3) was added to the 120 mL sodium hydroxide solution. The mixture was heated to 80°C and stirred for reaction for 24 hours. After the reaction, the solution was filtered and washed several times until the filtrate was neutral. After washing, the obtained solid was dried in an oven at 80°C for 12 hours. After drying, the solid was ground into powder to obtain a single-layer hollow carbon sphere with a particle size of 70 nm.

[0026] like Figure 5 As shown, the minimum reflection loss RL of this sample is when the paraffin filling ratio is 20% and the thickness is 2.5mm. min It reaches -16.81dB at 13.20GHz, and the effective absorption bandwidth EAB is 3.04GHz (11.44-14.48GHz).

[0027] Example 2 The other steps were the same as in Example 1, except that the amount of ammonia water used was 90 mL, and the particle size of the obtained single-layer hollow carbon spheres was 300 nm. Figure 6 As shown, the minimum reflection loss RL of this sample is when the paraffin filling ratio is 20% and the thickness is 2mm. min Reach -14.27dB at 13.20GHz, effective absorption bandwidth EAB is 4.00GHz (12.00-16.00GHz) Example 3 (1) Synthesis of silicon dioxide: 1500 mL of anhydrous ethanol, 210 mL of deionized water, 68.4 mL of ethyl orthosilicate, 800 mL of ammonia water and 0.4 g of potassium chloride were added to a beaker and mixed and stirred for 30 minutes to obtain a white silicon dioxide emulsion with a silicon dioxide particle size of 500 nm. Steps (2) to (4) were the same as in Example 1.

[0028] like Figure 7 As shown, the minimum reflection loss RL of this sample is when the paraffin filling ratio is 20% and the thickness is 2mm. min It reaches -19.87dB at 11.84GHz, and the effective absorption bandwidth EAB is 4.00GHz (14.56-14.56GHz).

[0029] Example 4 The other steps are the same as those in Example 3, except that when the amount of potassium chloride used is 1.0 g, the obtained silica particle size is 650 nm.

[0030] like Figure 8 As shown, the minimum reflection loss RL of this sample is when the paraffin filling ratio is 20% and the thickness is 2.5mm. min It reaches -8.17dB at 13.28GHz, and the effective absorption bandwidth EAB is 0.

[0031] Example 5 (1) Synthesis of silicon dioxide: 750 mL of anhydrous ethanol, 105 mL of deionized water, 34.2 mL of tetraethyl orthosilicate, 400 mL of ammonia water and 0.75 g of potassium chloride were added to a beaker and mixed for 30 minutes. Another 750 mL of anhydrous ethanol, 105 mL of deionized water, 34.2 mL of tetraethyl orthosilicate and 0.75 g of potassium chloride were mixed in another beaker and then added to the first beaker at a rate of 1 mL / min. The addition time was 900 min. The silicon dioxide particle size was 1000 nm. Steps (2) to (4) were the same as in Example 1.

[0032] like Fig. 9 As shown, the minimum reflection loss RL of this sample is when the paraffin filling ratio is 20% and the thickness is 2.5mm. min It reaches -8.32dB at 12.48, and the effective absorption bandwidth EAB is 0.

[0033] The SEM images of the single-layer hollow carbon spheres with different particle sizes obtained in Examples 1-5 are as follows: Figure 1 shown.

[0034] Example 6 (1) Synthesis of 500 nm silica: Add 1500 mL of anhydrous ethanol, 210 mL of deionized water, 68.4 mL of ethyl orthosilicate, 400 mL of ammonia water and 0.5 g of potassium chloride into a beaker and stir for 30 minutes to obtain a white silica emulsion.

[0035] (2) Synthesis of SiO2@RF: 12 g of resorcinol and 16.8 mL of formaldehyde were added to the silica emulsion obtained in step (1). The reaction was continued with stirring for 18 hours, and then the solid was centrifuged and dried in an oven at 80°C for 12 hours. The yellow SiO2@RF was then ground into powder using a mortar.

[0036] (3) Polyacrylic acid modified SiO2@RF: Add 60 mL of deionized water to 1 g of SiO2@RF powder ground in step (2), stir evenly, then add 1 g of polyacrylic acid and continue stirring to react for 3 hours. After the reaction is completed, the solution is centrifuged and washed with deionized water. The solid after centrifugation is dissolved in 60 mL of deionized water to obtain a solution modified with polyacrylic acid. Figure 4 This is the Fourier transform infrared spectrum of SiO2@RF before and after polyacrylic acid modification. It can be seen from the figure that the SiO2@RF before polyacrylic acid modification has a peak at 1456cm -1 、1540cm -1 、1612cm -1 The absorption peak at 800 cm-1 can be attributed to the skeleton vibration of the benzene ring in the phenolic resin, while the absorption peak at 800 cm-1 can be attributed to the skeleton vibration of the benzene ring in the phenolic resin. -1 This is attributed to the out-of-plane bending vibration of CH on the benzene ring in the phenolic resin; 1101cm -1 The absorption peak at 3205cm -1 The absorption peak at 3414cm is caused by the stretching vibration of the OH bond in the phenolic hydroxyl group of the phenolic resin. -1 1718cm -1 Absorption peaks appear at , which can be attributed to the stretching vibration of the OH bond in the carboxyl group and the stretching vibration of the C=O bond in the carboxyl group, respectively. This is the characteristic peak in the infrared spectrum of polyacrylic acid, proving that the modification of polyacrylic acid is successful.

[0037] (4) Synthesis of SiO2@RF@SiO2: The polyacrylic acid-modified solution in step (3) was added to 400 mL of ethanol, and then 20 mL of aqueous ammonia and 2 mL of tetraethyl orthosilicate were added in sequence. The mixture was stirred for 30 minutes to obtain an emulsion.

[0038] (5) Synthesis of SiO2@RF@SiO2@RF: 1.2 g of resorcinol and 1.68 mL of formaldehyde were added to the emulsion synthesized in step (4). The reaction was continued with stirring for 18 hours, and then the solid was centrifuged and dried in an oven at 80°C for 12 hours. The obtained solid was ground into powder using a mortar.

[0039] (6) Carbonization to form SiO2@C@SiO2@C: The ground powder in step (5) is placed in an alumina square porcelain boat, and then the alumina square porcelain boat is placed in a tubular furnace, connected to nitrogen, and the temperature is set to rise to 1000°C at a heating rate of 5°C / min, and carbonization reaction is carried out at 1000°C for 2 hours. When the temperature in the tubular furnace naturally cools down to room temperature, black SiO2@CSiO2@C is obtained.

[0040] (7) Removal of silica core: Take a slightly excess amount of sodium hydroxide and dissolve it in deionized water to obtain a 0.5 g / ml sodium hydroxide solution. Then add the SiO2@C@SiO2@C obtained in step (6) to the sodium hydroxide solution. The mass ratio of sodium hydroxide to SiO2@C@SiO2@C is 2:1. Heat to 80°C and stir to react for 24 hours. After the reaction is completed, the solution is filtered and washed several times until the filtrate is neutral. After washing, the obtained solid is dried in an oven at 80°C for 12 hours. After drying, the solid is ground into powder to obtain a double-layer hollow carbon sphere. The TEM image is shown in FIG. Figure 3 As shown in b.

[0041] like Fig.10 As shown, the minimum reflection loss RL of this sample is when the paraffin filling ratio is 20% and the thickness is 2.5mm. min It reaches -43.87dB at 9.60GHz, and the effective absorption bandwidth EAB is 6.00GHz (8.64-14.64GHz).

[0042] Example 7 Take 1 g of the powder obtained in step 5 of Example 4 and carry out the operation steps from step (3) to step (7) of the example to obtain a three-layer hollow carbon sphere. The TEM image is shown in FIG. Figure 3 As shown in c.

[0043] like Fig.11 As shown, the minimum reflection loss RL of this sample is 20% when the paraffin filling ratio is 20% and the thickness is 2.0 mm. min It reaches -20.49dB at 11.76GHz, and the effective absorption bandwidth EAB is 4.00GHz (10.08-14.08GHz).

[0044] Comparative Example 1 The specific steps are the same as those in Example 6, except that polyacrylic acid is not added in step (3); the results are as follows Figure 2 As shown, a double-layer hollow structure cannot be obtained without adding polyacrylic acid for modification.

[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a multilayer carbon sphere material, characterized in that: The multilayer carbon sphere material has silicon dioxide as a core and polyacrylic acid-modified phenolic resin as a shell. The multilayer hollow carbon sphere is obtained by repeatedly and alternately wrapping silicon dioxide and phenolic resin, carbonizing them, and then removing the silicon dioxide core.

2. The preparation method according to claim 1, characterized in that: The particle size of the silicon dioxide is 70-1000 nm.

3. The preparation method according to claim 1, characterized in that: The specific steps are as follows: (1) Synthesis of silicon dioxide: Anhydrous ethanol, deionized water, ethyl orthosilicate, ammonia water and potassium chloride are mixed and stirred to obtain a silicon dioxide emulsion; (2) Synthesis of SiO2@RF: resorcinol and formaldehyde were added to the silica emulsion obtained in step (1), stirred for reaction for 18 h, and then centrifuged. The obtained solid was dried at 60-80°C for 12 h and crushed to obtain SiO2@RF powder. (3) Polyacrylic acid modified SiO2@RF: After dissolving SiO2@RF powder in deionized water, polyacrylic acid was added to react. After the reaction, the solution was centrifuged and the washed solid was redissolved in deionized water to obtain a polyacrylic acid modified SiO2@RF solution. (4) Synthesis of SiO2@RF@SiO2: add anhydrous ethanol, aqueous ammonia and ethyl orthosilicate to the solution obtained in step (3) and stir for 30 minutes to obtain an emulsion; (5) Synthesis of SiO2@RF@SiO2@RF: Add resorcinol and formaldehyde to the emulsion obtained in step (4), stir and react for 18 hours, then centrifuge. The obtained solid is dried at 60-80°C for 12 hours and crushed to obtain SiO2@RF@SiO2@RF powder. (6) Carbonization to form SiO2@C@SiO2@C: The powder obtained in step (5) is placed in a tube furnace, heated to 1000°C at a heating rate of 5°C / min in a nitrogen atmosphere, and reacted for 2 hours. After cooling to room temperature, SiO2@C@SiO2@C is obtained; (7) placing the SiO2@C@SiO2@C obtained in step (6) in an aqueous sodium hydroxide solution and reacting at 80°C for 24 hours, filtering the solution after the reaction, washing it to neutrality, and drying it to obtain double-layer hollow carbon spheres; (8) Repeat steps (3) to (7) with the SiO2@RF@SiO2@RF obtained in step (7) to obtain a three-layer hollow carbon sphere.

4. The preparation method according to claim 3, characterized in that: In step (1), the amount of anhydrous ethanol, deionized water, tetraethyl orthosilicate, ammonia water, and potassium chloride is 1500 mL: 210 mL: 68.4 mL: (20-200 mL): (0.2-1.4 g).

5. The preparation method according to claim 3, characterized in that: In step (2), the amount of resorcinol and formaldehyde used is 12 g:16.8 mL.

6. The preparation method according to claim 3, characterized in that: In step (3), the ratio of SiO2@RF powder to polyacrylic acid is 1:

1.

7. The preparation method according to claim 3, characterized in that: In step (4), the dosage ratio of anhydrous ethanol, aqueous ammonia and ethyl orthosilicate is 200 mL:10 mL:1 mL.

8. The preparation method according to claim 3, characterized in that: The concentration of the sodium hydroxide solution in step (7) is 0.5 g / mL.

9. Multilayer hollow carbon spheres obtained by the preparation method according to any one of claims 1 to 8.

10. A method for adjusting the particle size of silicon dioxide, characterized in that: The specific steps are as follows: (1) Synthesis of 70-450nm silica particles: 1500mL of anhydrous ethanol, 210mL of deionized water, 68.4mL of ethyl orthosilicate and ammonia water were added into a beaker and stirred for 30 minutes. After the reaction was completed, a white silica emulsion was obtained. The amount of ammonia water was adjusted from 20mL to 200mL, and the silica particle size was increased from 70nm to 450nm. (2) Synthesis of silica with a particle size of 450-800 nm: 1500 mL of anhydrous ethanol, 210 mL of deionized water, 68.4 mL of ethyl orthosilicate, 800 mL of ammonia water and potassium chloride were added to a beaker and stirred for 30 minutes to obtain a white silica emulsion. The amount of potassium chloride was adjusted from 0.2 to 1.4 g, and the silica particle size was adjusted from 450 nm to 800 nm. (3) Synthesis of 800-1000 nm silica particle size: Add 750 mL of anhydrous ethanol, 105 mL of deionized water, 34.2 mL of tetraethyl orthosilicate, 400 mL of ammonia water and 0.75 g of potassium chloride into a beaker and mix and stir for 30 minutes. Then, add another 750 mL of anhydrous ethanol, 105 mL of deionized water, 34.2 mL of tetraethyl orthosilicate and 0.75 g of potassium chloride into another beaker and add them into the first beaker at a rate of 1 mL / min. The addition time was adjusted from 0 to 900 min. The silica particle size ranged from 800 nm to 1000 nm.

Citation Information

Patent Citations

  • Microwave preparation method for monodisperse size-adjustable hollow porous carbon-spheres

    CN106167255A

  • Preparation method of hollow carbon microspheres and hollow carbon microspheres obtained by method

    CN108059143A

  • Carbon-coated hollow silicon dioxide composite material and preparation method thereof

    CN112897536A

  • Hollow porous carbon sphere ultra-black material and preparation method thereof

    CN119284883A

  • Method for producing carbon material utilizing inorganic template particle and having nanopore

    JP2001233674A

Cited By

  • A multi-level pore hollow carbon sphere and a preparation method and application thereof

    CN122667553A